De Bispo A Santo? Cipriano De Cartago Como Um Bispo-Mártir Exemplar Na Vita Cypriani, De Pôncio - Godoy, Victor Andrade [UNIFESP] (2017)
In this study, we seek to analyze a narrative dedicated to the life and death of Saint Cyprian of Carthage, converted to the Christian faith in the vicinity of 246, elected bishop near 248-49, and crowned as a martyr in 258: the Vita Cypriani, which his deacon, Pontius, composed at the end of the decade of 250 in order to render saintly or exemplary his life as a bishop and his death as a martyr. Firstly, we intent to understand which new meanings Pontius gave to which well-known events to defend Cyprian (accused of having fled from Carthage during the implantation of Decius's edict due to a fear of martyrdom) and to laud his life and death in order to offer to posterity the memory of a double example of a bishop-martyr which could incite imitation of itself amongst the Christians. We also aim at analyzing the three elements in which Pontius composed the memory of the double example of a bishop-martyr given by Cyprian in the course of his life and at the moment of his death, namely: his lessons on the unity of the Church, his acts of charity, and his martyrial death. At last, we wish to understand the behavioral change that Pontius tried to elicit in his interlocutors through the imitation of such lessons, acts and death. To do this, we will bear in mind the texts which Pontius read and used to compose the Vita Cypriani, namely: the letters and the sermons penned by the bishop-martyr, the Passio Perpetuae, and the Acta Cypriani.